A New Authentication Scheme with Elliptical Curve Cryptography for Internet of Things (IoT) Environments - Durairaj, M; Muthuramalingam, K (International Journal of Engineering and Technology, 2018)
Internet of Things (IoT) consists of a large number of connected objects that are communicating with each other. To support trusted communication between IoT objects, the authentication procedures should be used and applied to the communicating entities. Internet of Things (IoT) is an emerging technology, which makes the remote sensing and control across the heterogeneous network a reality, and has good prospects in industrial applications. As an essential infrastructure, Wireless Sensor Networks (WSNs) play a crucial role in industrial IoT. Due to the resource-constrained feature of sensor nodes, the design of security and efficiency balanced authentication scheme for WSNs becomes a significant challenge in IoT applications. In this paper, an anonymous authentication scheme for WSNs in an Internet of Things environments.Â Â